Performance Evaluation of the Plagiarism Systems A Systematic Review - Nawzt Hasan Qazan; Shayma Mustafa Al- Mashhadany (Universitas Khairun, 2023)
Paraphrase plagiarism occurs when text is deliberately obfuscated to evade detection, deliberate alteration increases the complexity of plagiarism and the difficulty in detecting paraphrase plagiarism., Plagiarism systems play an important role in educational and research institutions. In the field of education, the use of these systems has increased in universities to help researchers select new research, which is why it has been important to ensure that universities have effective citation screening systems. Different metrics were used to evaluate the performance of these systems. All of these metrics affect the performance and usability of the impersonation system. This paper present a systematic literature review (SLR) to obtain an overview of the existing studies of distinct criteria for evaluating the performance of textual plagiarism systems and each criterion is briefly explained to give the basic idea behind it. Overall, the aim of this paper is to provide a modern introduction and short review of these criteria. A systematic literature review is performed according to the guidelines for conducting SLR in software engineering. The study relied on a comprehensive set of research papers collected from electronic libraries published during a time period from 2013 to 2023. The results of this SLR include information about metrics for evaluating the performance of plagiarism systems according to previous research. During a specific period it can assist researchers in this field by providing an overview of current researches in this field. Moreover, it may serve as a first step towards a great SLR-assisted explanation of the subject.